Practices and determinants of urban land governance in Sheger City, Ethiopia - Nigatu, Degu Bekele (Frontiers in Sustainable Cities, 2024)
While there have been numerous global discussions on urban land governance, a lot remains to be done and serious urban land related obstacles remain to be overcome. This article identifies the most important governance principles for improving land governance for urban development and growth. The governance principles assessed in this study include participation, responsiveness, efficiency, openness, rule of law, rule of ethics, completeness, innovation, sustainability, sound financial management, sound human rights and accountability. Source of primary data is 458 households and secondary data was collected from policy documents and regional government reports. The governance level is measured by using seven point likert scale and the results reveal that the status of land governance in Sheger City is lower (3.445) than the average level which is 3.5 (50%). Out of the twelve independent variables, the mean score of only four, meaning innovation and openness to change (3.74), openness and transparency (3.68), competence and capacity (3.51), and rule of law (3.52), is more than 50%. The remaining eight variables are below the average, indicating poor land governance in Sheger City. Regarding the determinants, 76.21% of the variation in land governance in Sheger city is explained by the model applied. The highest beta value is registered for responsiveness, and the next highest is for innovation and openness to change. These findings have important implications for policymakers and urban planners in Ethiopia, highlighting the need for continued efforts to improve urban good governance and land management practices to ensure sustainable and equitable urban development.